Just Shake Them Together: Imitation-Resistant Secure Pairing of Smart Devices via Shaking. (5th April 2021) - Shi, Congcong; Xie, Lei; Wang, Chuyu; Yang, Peicheng; Song, Yubo; Lu, Sanglu
Abstract : In traditional device-to-device (D2D) communication based on wireless channel, identity authentication and spontaneous secure connections between smart devices are essential requirements. In this paper, we propose an imitation-resistant secure pairing framework including authentication and key generation for smart devices, by shaking these devices together. Based on the data collected by multiple sensors of smart devices, these devices can authenticate each other and generate a unique and consistent symmetric key only when they are shaken together. We have conducted comprehensive experimental study on shaking various devices. Based on this study, we have listed several novel observations and extracted important clues for key generation. We propose a series of innovative technologies to generate highly unique and completely randomized symmetric keys among these devices, and the generation process is robust to noise and protects privacy. Our experimental results show that our system can accurately and efficiently generate keys and authenticate each other.